Centromeres of the Yeast Komagataella phaffii (Pichia pastoris) Have a Simple Inverted-Repeat Structure. (10th July 2016) - Coughlan, Aisling Y.; Hanson, Sara J.; Byrne, Kevin P.; Wolfe, Kenneth H.
Abstract : Centromere organization has evolved dramatically in one clade of fungi, the Saccharomycotina. These yeasts have lost the ability to make normal eukaryotic heterochromatin with histone H3K9 methylation, which is a major component of pericentromeric regions in other eukaryotes. Following this loss, several different types of centromere emerged, including two types of sequence-defined ("point") centromeres, and the epigenetically defined "small regional" centromeres of Candida albicans . Here we report that centromeres of the methylotrophic yeast Komagataella phaffii (formerly called Pichia pastoris ) are structurally defined. Each of its four centromeres consists of a 2-kb inverted repeat (IR) flanking a 1-kb central core ( mid ) region. The four centromeres are unrelated in sequence. CenH3 (Cse4) binds strongly to the cores, with a decreasing gradient along the IRs. This mode of organization resembles Schizosaccharomyces pombe centromeres but is much more compact and lacks the extensive flanking heterochromatic otr repeats. Different isolates of K. phaffii show polymorphism for the orientation of the mid regions, due to recombination in the IRs. CEN4 is located within a 138-kb region that changes orientation during mating-type switching, but switching does not induce recombination of centromeric IRs. Our results demonstrate that evolutionary transitions in centromere organization have occurred in multiple yeast clades.